5(r-8)-4(6r-4)=-8r-8r

Simple and best practice solution for 5(r-8)-4(6r-4)=-8r-8r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(r-8)-4(6r-4)=-8r-8r equation:


Simplifying
5(r + -8) + -4(6r + -4) = -8r + -8r

Reorder the terms:
5(-8 + r) + -4(6r + -4) = -8r + -8r
(-8 * 5 + r * 5) + -4(6r + -4) = -8r + -8r
(-40 + 5r) + -4(6r + -4) = -8r + -8r

Reorder the terms:
-40 + 5r + -4(-4 + 6r) = -8r + -8r
-40 + 5r + (-4 * -4 + 6r * -4) = -8r + -8r
-40 + 5r + (16 + -24r) = -8r + -8r

Reorder the terms:
-40 + 16 + 5r + -24r = -8r + -8r

Combine like terms: -40 + 16 = -24
-24 + 5r + -24r = -8r + -8r

Combine like terms: 5r + -24r = -19r
-24 + -19r = -8r + -8r

Combine like terms: -8r + -8r = -16r
-24 + -19r = -16r

Solving
-24 + -19r = -16r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '16r' to each side of the equation.
-24 + -19r + 16r = -16r + 16r

Combine like terms: -19r + 16r = -3r
-24 + -3r = -16r + 16r

Combine like terms: -16r + 16r = 0
-24 + -3r = 0

Add '24' to each side of the equation.
-24 + 24 + -3r = 0 + 24

Combine like terms: -24 + 24 = 0
0 + -3r = 0 + 24
-3r = 0 + 24

Combine like terms: 0 + 24 = 24
-3r = 24

Divide each side by '-3'.
r = -8

Simplifying
r = -8

See similar equations:

| 2x=5x+21-6 | | 3(1+11)= | | 5a^2+60a+180=0 | | 3x^2-18x-19=0 | | 2(1+x)=3(x+4) | | 9x+70=360 | | 2x(x-4)(x+8)=0 | | 3(5p-3)=5(p-1) | | 14x-3(2x-5)+2(5x-3)=6-5(2x-9) | | 3(y+30)=6y-4 | | 5(v-5)+3(v+2)=-4v+7+3v-2 | | 3(x+5)=5x+2.5 | | 117=6x-12+3x+3 | | (34-2)y=8 | | 8(5x-3)+4(1-8x)=3x-8+3x-2 | | 4u^2-2u=0 | | 10x5/2 | | 2p-10)/(8p-40) | | 6(9d)=3d | | 180=x+(0.05+x) | | (9x-2y)-(6x+2y)= | | 6(x-4)-4=8 | | 4logx-3logx=12 | | 238=16t^2+32t | | Xy=5x-2 | | x=13+0.75y | | 4lgx^3-3lgx^2=12 | | (5x-3)/3=4 | | 4logx^3-3logx^2=12 | | (-7)=g+(-5) | | 5a+1=8 | | 5a+56=-56 |

Equations solver categories